2021
DOI: 10.1038/s41398-021-01416-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the psychiatric symptoms of COVID-19: a meta-analysis of studies assessing psychiatric symptoms in Chinese patients with and survivors of COVID-19 and SARS by using the Symptom Checklist-90-Revised

Abstract: Understanding the psychiatric symptoms of COVID-19 could facilitate the clinical management of COVID-19 patients. However, the profile of psychiatric symptoms among COVID-19 patients has been understudied. We performed a meta-analysis of studies assessing psychiatric symptoms of COVID-19 and SARS patients and survivors by using the Symptom Checklist-90-Revised (SCL-90-R), an instrument covering a wide spectrum of psychiatric symptoms. Studies reporting SCL-90-R subscale scores among patients with and survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
3
27
0
1
Order By: Relevance
“…While the patterns of mortality incidence in this study could be attributed to exogenous societal and economic factors, it is possible that endogenous factors of COVID-19 infection also played a role. SARS-CoV-2 can cross the blood brain barrier and increase the risk of neurological and psychiatric outcomes, 58 especially among those with more severe forms of COVID-19 (e.g., hospitalization, intubation). 59 Patterns within demographic groups might represent disparate levels of infection.…”
Section: Discussionmentioning
confidence: 99%
“…While the patterns of mortality incidence in this study could be attributed to exogenous societal and economic factors, it is possible that endogenous factors of COVID-19 infection also played a role. SARS-CoV-2 can cross the blood brain barrier and increase the risk of neurological and psychiatric outcomes, 58 especially among those with more severe forms of COVID-19 (e.g., hospitalization, intubation). 59 Patterns within demographic groups might represent disparate levels of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have previously suggested that medical patients suffering from acute life-threatening diseases may exhibit moderate to severe psychiatric symptoms [ 8 ]. A significant proportion (36.4%) of our cohort exhibit signs and symptoms of obsessive-compulsive disorder, 22.7% demonstrated signs of depression and hostility, and 18.2% presented high interpersonal sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of psychiatric symptoms are present in acute medical patients suffering from potentially lethal diseases [ 8 ]. The psychological characteristics may relate to physical symptoms and influence how patients manage their disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the end of 2021, 278,714,484 cases of COVID-19 had been reported worldwide [1]. As the coronavirus disease 2019 (COVID-19) has rapidly spread worldwide, mental health among patients with COVID-19 is an emerging and important public health issue [2][3][4].…”
Section: Introductionmentioning
confidence: 99%